Cold-induced Anaphylaxis: The Case of a 9-year-old Child and Review of the Literature - Romita, Paolo; Mascia, Paola; Calogiuri, Gianfranco; Foti, Caterina (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2017)
Background and Objective: The present review investigated cold-induced anaphylaxis, a potentially life-threatening condition that occurs after exposure to cold stimuli and is characterized by respiratory distress and/or hypotension. Anaphylaxis is rarely associated to cold-induced urticarial (CU), a particular form of physical urticaria that is difficult to diagnose and manage. The incidence of cold-induced urticaria has been estimated at about 0.05%, higher in colder regions and in women; its pathological mechanisms are still unknown. Methods: The literature was searched via the Medline/PubMed database (http://www.ncbi.nlm.gov/ pubmed). Results and Conclusion: Patients affected by CU should be well-informed about the risk of anaphylaxis and preventive measures. The prevention of CU is based on the avoidance of cold exposure. The most effective treatment is antihistamines symptomatic therapy. Anyway, patients should also carry with them an emergency kit containing corticosteroids, antihistamines and an epinephrine injector. Future studies are necessary to determine the CU pathophysiology so to establish a more targeted management of this important and potentially life-threatening condition.
Keywords: urticaria